TUNA KELEŞTEMUR. G. and ÖZDEMIR, Y., 2013. Effects of Dietary Vitamin A and Eon Growth performance and Antioxidant status in blood of juvenile rainbow trout (oncorhynchus mykiss, w. 1792) exposed to flow rate stress. - Tuna Keleştemur, Gülüzar, Yaşar Özdemir (My University, 2013)
The present study investigated the effects of vitamin A and E supplementation in diets of juvenile rainbow trout subjected to two different flow rates with or without flow stress (0.9 and 2.1 l/min, respectively) on growth performance, vitamin A and E concentrations in serum, malondialdehyde (MDA) level in serum as well as plasma SOD (superoxide dismutase) activity. Fish fed with the three experimental diets (30E+A, 60E+A, –E+A ) during 12 weeks. In the unstressed groups, WG (weigth gain) of fish did not differ among the diets groups (p>0.05). Lower WG was observed in fish fed the vitamin E-free diet in stressed groups (p<0.05). In stress and unstressed groups, SGR (specific growth rate) was not different among all dietary treatments (p<0.05). In stressed group, SUR (survivor rate) was highly significant in A+60E and A+30E groups and lower SUR was observed in fishes in the A-E group (P<0.05). Both flow rate trials, there was no significant difference in serum vitamin A concentration of all diet groups (p>0.05). In the unstressed and stressed groups, serum vitamin E concentration was lowest in fish fed with A-E diets (p<0.05). In the unstressed and stressed groups, serum MDA (malondialdehyde) level was highest in fish fed the A-E diet (p<0.05). In the unstressed group, SOD activity were similarly affected by 30 and 0 mg/kg vitamin E supplemented diet groups and in both stress conditions plasma SOD (superoxide dismutase) enzyme activity increased in A+60E diet group.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: rainbow trout; stress; growth performance; antioxidan status.